The regional distribution of foreign investment in Russia1. Issue 4 (15th June 2014) - Gonchar, Ksenia; Marek, Philipp
Abstract This article conducts a plant‐level study of the factors affecting foreign direct investment (FDI) inflow to a large opening economy endowed with specific factor advantages. We conclude that the distribution of FDI in Russian regions depends on market access and can be most notably described by the knowledge‐capital framework. Factor endowments built by natural resources are more successful in explaining the location decisions of export–platform affiliates. The impact of natural resources depends on how the availability of these resources is measured. The results reject the crowding out effects of resource FDI and prove co‐location mode, when service investments are attracted to resource‐rich regions. Labour cost advantages better explain the preferences of non‐trading service affiliates.